Perbandingan Efektivitas Bermain Plastisin dengan Finger Painting terhadap Perkembangan Motorik Halus Anak Prasekolah - Harsismanto J; Agus Ramon; Remo Putrawan; Padila Padila; Juli Andri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the comparison of the effectiveness of playing plasticine with finger painting on the fine motor development of pre-school children at PAUD Dharma Wanita Persatuan Bengkulu City. This type of research is a quantitative research with a Quasi Experimental design. The results showed that before the intervention, there were 8 (53.3%) children whose fine motor development was included suspect in the finger painting group, and 7 (46.7%) children were in the suspect category in the plasticine playing group. After being given the intervention by playing plasticine, there were 10 people (66.6%) whose fine motor development was normal, while the respondents after being given intervention by playing finger painting were 14 children (93.3%) whose fine motor development was normal. The results of the Wilcoxon test showed that the p-value of the two groups was 0.043 for the plasticine group and 0.007 for the finger painting group, which means that there was a difference in the average score for the fine motor category before and after the intervention was given to the two groups. Based on the results of the Mann-Whitney test, the p value = 0.073. In conclusion, the two interventions were statistically effective in increasing the average score of the fine motor ability category of preschool children and there was no significant difference in the effectiveness of the two intervention groups in increasing the average score of the fine motor ability category of preschool children in PAUD Dharma Wanita Persatuan Bengkulu City. Keywords: Finger painting , Fine Motor, Plasticine